1995
DOI: 10.1093/ajcp/104.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Clonal VDJ Recombination of the Immunoglobulin Heavy Chain Gene by PCR in Classical Hodgkin’s Disease

Abstract: Although Hodgkin's disease (HD) has been a subject of much investigation, fundamental questions remain unanswered regarding its lineage and clonality. The authors used a polymerase chain reaction (PCR) technique to investigate whether clonal Variable-Diversity-Joining recombination of the immunoglobulin heavy (IgH) chain gene, a phenomenon that characterizes clonal B-cell proliferations, exists in nodular sclerosing (NSHD) and mixed cellularity (MCHD) Hodgkin's disease (so-called "classical" Hodgkin's disease)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Only a handful of publications have described PCR-based clonality detection for HL using non-microdissected specimens 3, 5, 8-10, 4. Just 3 of these have assessed the use of the standardized BIOMED-2 primer system for FFPE HL specimens (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of publications have described PCR-based clonality detection for HL using non-microdissected specimens 3, 5, 8-10, 4. Just 3 of these have assessed the use of the standardized BIOMED-2 primer system for FFPE HL specimens (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30 per cent of cases of classic HD showed IgH chain gene rearrangement, in overall agreement with reports using similar techniques but with a smaller number of cases. [5][6][7][8] Complete rearrangement of the IgH gene signifies commitment to B-lymphocyte lineage. 9 The study of TcR-gene rearrangements has practical implications, since TcRgenes have a limited V gene repertoire, despite extensive 23,[32][33][34] In addition, TcR-gene rearrangement occurs at an early stage of T-lymphocyte development and can be exploited as a marker of clonality in almost all T-lymphoid neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The low detection rate of Ig and TcR gene rearrangements by Southern blotting has been attributed to either the paucity of tumour cells below the detection threshold or the actual absence of such gene rearrangements, leaving widely divergent possibilities for the derivation of HRS cells. With the use of the more sensitive and specific polymerase chain reaction (PCR), rearranged Ig heavy chain (IgH) genes have been detected recently in 25-50 per cent of classic HD (non-lymphocyte predominant subtypes), [5][6][7][8] supporting a clonal lymphocytic origin in a proportion of HD cases. While the current investigation on the study of HD by PCR using consensus primers was in progress, two groups confirmed the presence of Ig gene rearrangements in selected cases of HD in single HRS cells isolated by micromanipulation from frozen sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial fraction of RS cells express lymphoid antigens; approximately 15% to 38% express CD20, and 11% to 24% express CD3. [27][28][29] Although early studies detected clonal immunoglobulin heavy chain gene rearrangements in RS cells in only 50% of cases, [27][28][29][30] individual cell micromanipulation and PCR have permitted the identification of clonal immunoglobulin heavy chain gene rearrangements in 90% to 95% of HD cases, with evidence of somatic mutation suggestive of germinal center origin. [31][32][33][34] Because most cases of HD are presumed to arise from the B-cell lineage, it is not surprising that a high incidence of other B-cell lymphomas is seen.…”
mentioning
confidence: 99%